Reassessing the validity of using weighted linear models to implement multi-generational GWAS-by-subtraction: a response to Evans et al. - Benjamin Woolf; Dipender Gill; Marcus Munafò; Stephen Burgess (BMC Research Notes)
Abstract Evans and colleagues for providing a critique on our article “Deriving GWAS summary estimates for paternal smoking in UK biobank: a GWAS by subtraction”. They highlight important limitations in our approach, which we overlooked. They argue that our approach works neither in theory nor in practice– that there are both flaws in the method and in our execution of the method. Here we explore these issues and address what we consider to be the most important criticisms.